2(x+4)-2=5x-3(-1+x)

Simple and best practice solution for 2(x+4)-2=5x-3(-1+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+4)-2=5x-3(-1+x) equation:


Simplifying
2(x + 4) + -2 = 5x + -3(-1 + x)

Reorder the terms:
2(4 + x) + -2 = 5x + -3(-1 + x)
(4 * 2 + x * 2) + -2 = 5x + -3(-1 + x)
(8 + 2x) + -2 = 5x + -3(-1 + x)

Reorder the terms:
8 + -2 + 2x = 5x + -3(-1 + x)

Combine like terms: 8 + -2 = 6
6 + 2x = 5x + -3(-1 + x)
6 + 2x = 5x + (-1 * -3 + x * -3)
6 + 2x = 5x + (3 + -3x)

Reorder the terms:
6 + 2x = 3 + 5x + -3x

Combine like terms: 5x + -3x = 2x
6 + 2x = 3 + 2x

Add '-2x' to each side of the equation.
6 + 2x + -2x = 3 + 2x + -2x

Combine like terms: 2x + -2x = 0
6 + 0 = 3 + 2x + -2x
6 = 3 + 2x + -2x

Combine like terms: 2x + -2x = 0
6 = 3 + 0
6 = 3

Solving
6 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (8x+30)+(4x+18)=180 | | 7ln(x-3)=1 | | 10b^2+17b+3= | | 41.5=6x-3.5 | | 0=5x^2-36 | | -0.10(28)+0.30x=0.05(x-6) | | 11y+16=42-2y | | 4f+13g(2w)= | | 17-8v=-3(5+8v) | | y^2-xy-56x^2= | | 3x+8y+13= | | 3x^2-12x=-9 | | y=6x-3.5 | | -5(1+4x)+1=x+38 | | -5(3p-3)-5(3-3p)=-4p-5p | | x^2+42-135=0 | | t+2=26-2t | | 30=x/7-20 | | 3(4x+4)=6(x+1)+4x | | 34+2n=8(n+5) | | 9x-(5x+9)=4x-24 | | -1/4=2.4x+10-0.35x | | 6x+7=103 | | 3x-3x=-4x | | b-2=b+6+2-10 | | x-3-8x=-24 | | 1/2(-2x-7)=3/4 | | 2x-15=3-x | | cosx^2-cosx=0 | | 8(1+5k)=8(1-7k) | | y=(-13/16)-1/4 | | 6(5x-6)=6(6x+8) |

Equations solver categories